Rules of Thumb for Evaluating Preferential Trading Arrangements : Evidence from Computable General Equilibrium Assessments - Harrison, Glenn W.; Rutherford, Thomas F.; Tarr, David G. (World Bank, Washington, DC, 2014)
Most interesting results on the welfare effects of regional arrangements are ambiguous at a theoretical level. Many questions only have quantitative answers that are specific to the particular structural features of the economy and the policy considered. So, to determine the impact of prospective regional arrangements governments often rely on a quantitative evaluation. Usually at the request of client governments of the World Bank, the authors have implemented many computable general equilibrium (CGE) models to inform policymakers. The authors summarize the main conclusions drawn from these studies. The principal conclusions are: 1) Countries excluded from a preferential trade arrangement almost always lose. 2) Market access is a key determinant of the net benefits of a preferential trade arrangement. 3) With a free trade agreement (FTA) the external tariff can be lowered such that a poor FTA becomes attractive. 4) For Southern countries, North-South agreements offer a beneficial increase in competition in their home markets, and involve little increase in the supply price of Northern country sales in Southern countries. 5) Multilateral trade liberalization results in significantly larger gains to the world than the network of regional arrangements. 6) For individual countries without high protection, "additive regionalism" will likely result in substantially larger gains than unilateral trade liberalization. 7) Tax replacement requirements reduce the set of desirable regional arrangements. 8) Trade taxes are often an inefficient source of tax revenue. 9) Trade liberalization should be expected to be pro-poor in developing countries, but results will be diverse at the household level so safety nets are important. 10) Dynamic effects to reverse conclusions regarding regionalism are not expected.